Electrical transport and thermoelectric properties of double filled compounds Ca0.1CexCo4Sb12 at low temperatures - Li, D. (2014)
The electrical transport and thermoelectric properties of CoSb3 and double filled compounds Ca0.1CexCo4Sb12 (x=0.05, 0.1, and 0.15) were investigated in the temperature range from 5 to 300 K. The results indicated that double filling of Ca and Ce has a strong influence on the temperature dependence of the electrical resistivity. For samples CoSb3 and Ca0.1Ce0.05Co4Sb12, the relationship of ln ρ∝1/T existed only in the temperature regimes of 100–200 and 160–300 K, respectively, while Mott’s law ln ρ∝T-1/4 was obeyed at lower temperatures below 100 and 160 K for CoSb3 and Ca0.1Ce0.05Co4Sb12, respectively. The results suggested a localization of charge carriers. Moreover, a transition from the semiconducting state (i.e., dρ/dT<0) (x=0.05) to the metallic state (i.e., dρ/dT>0) (0.05<x ≤0.15) took place owing to heavy filling. Due to the increase in carrier concentration, the electrical resistivity for Ca0.1CexCo4Sb12 (x>0.5) was observed to be smaller than that of CoSb3. However, the increase in carrier concentration did not affect the absolute Seebeck coefficient values. In fact, a large absolute Seebeck coefficient was maintained, which was likely due to the large effective mass arising from the filler atoms. Moreover, the low-temperature lattice thermal conductivity of Ca0.1CexCo4Sb12 was observed to decrease monotonously with increasing Ce content, which was attributed to the rattling motion of the Ca and Ce atoms in the Sb cages. As a result, the figure of merit, ZT, of heavily filled compounds Ca0.1CexCo4Sb12 (x=0.1 and 0.15) improved over the whole temperature range investigated. In particular, ZT of Ca0.1Ce0.15Co4Sb12 was tenfold larger than that of CoSb3 at 300 K. The current results showed that double filling Ca and Ce is an efficient way in improving the thermoelectric properties.